Kebiasaan merokok keluarga serumah dan pneumonia pada balita - Rony Darmawansyah Alnur; Djauhar Ismail; Retna Siwi Padmawati (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
The correlation of family smoking habits at home with the incidence of pneumonia among children in Bantul district in 2015PurposeThis study aimed to analyze the association between family smoking habits at home with the incidence of pneumonia in children.MethodsThis research was a case control study involving 160 children in the district of Bantul (80 with pneumonia and 80 without pneumonia).ResultsThere was an association between family smoking habits at home with the incidence of pneumonia in children at Bantul. Furthermore, it was found the other variables that had a association with the incidence of pneumonia in children at Bantul District included the use of mosquito coils, nutritional status of children and crowded household. The variables of maternal education, immunization status, income parents, history of exclusive breastfeeding, history of vitamin A, the type of household fuel, the location of the kitchen, the type of house walls and the activity of burning trash were not associated with the incidence of child pneumonia in the district of Bantul.ConclusionIt is necessary to conduct health promotion in all households about the impact of family smoking habits on children, especially in a crowded household. Also, there is need to supervise the family members who have the habit of smoking so the are not smoking inside the house, especially in families with children. It is equally important to repair any lowered nutrition status in children.